DETERMINATION OF THE INFLUENCE OF PREVIOUS DEFORMATIONS ON THE RESISTANCE OF SPECIAL SHOES TO MULTIPLE BENDING - NADOPTA, TETYANA; MYKHAILOVSKA, OKSANA; OLIYNYK, ANASTASIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article examines the concept of natural leather deformation on its resistance to multiple bending for special military footwear. Durability of special shoes for military personnel is directly related to the product’s resistance to repeated deformations. Such shoes are subject to significant deformations, as they are intended for extreme conditions of operation, as well as significant physical loads, causing the respective bending of the parts of the shoes, especially vamps. As a result of studies of natural leather of the chrome tanning method (heifer light and horsehide of the chrome tanning method) regarding resistance to bending, it has been established that durability of leather, excluding the influence of operational deformations, also decreases due to changes in the structure and properties of the leather under the influence of the previous deformation by stretching during the process of leather manufacture. The obtained results will be taken into account when designing and improving technological processes of manufacturing special shoes for military personnel.